2021
DOI: 10.1088/1755-1315/674/1/012059
|View full text |Cite
|
Sign up to set email alerts
|

Study of bivalvia habitat in the mangrove area of Aceh Jaya District, Aceh Province

Abstract: One of the biota that utilizes the mangrove ecosystem as its habitat is a group of Bivalvia belonging to the Phylum Mollusca Class Pelecypoda (Bivalvia). Shellfish have relatively high economic and nutritional value, so that the collection of shellfish in Aceh Jaya District continues. The research was conducted to study the biological components, analyze the habitat preferences, and management patterns of shellfish in the mangrove area of Aceh Jaya Regency. The research was conducted by using purposive samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…In the northern part of Sumatra (Aceh Province), a group of researchers studied the habitat characteristics of bivalve molluscs in a downstream (tidal) section of a river, with a special focus on mangroves (Heriansyah et al, 2020; Hermi et al, 2021). Among typical estuarine species, the team discovered what they thought was a population of S. woodiana .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the northern part of Sumatra (Aceh Province), a group of researchers studied the habitat characteristics of bivalve molluscs in a downstream (tidal) section of a river, with a special focus on mangroves (Heriansyah et al, 2020; Hermi et al, 2021). Among typical estuarine species, the team discovered what they thought was a population of S. woodiana .…”
Section: Resultsmentioning
confidence: 99%
“…In our opinion, this tendency may adversely affect conservation efforts for endangered taxa and the management of invasive species that are necessary to reverse biodiversity losses (Harper et al, 2021). For example, it was suggested that S. woodiana is a dominant and frequently occurring bivalve species in mangrove areas of North Sumatra within a salinity range of 3-15 ppt (Hermi et al, 2021) and 0-7 ppt (Heriansyah et al, 2020). Based on these observations, the authors conclude that S. woodiana is a euryhaline species, as are many other bivalves.…”
Section: Discussionmentioning
confidence: 99%
“…Sinanodonta woodiana atau Anodonta woodiana (Gabka et al, 2007) merupakan salah jenis kerang dari filum moluska kelas bibalvia, (Heriansyah et al, 2020;Hermi, 2020;Mursawal et al, 2022). Kerang ini termasuk dalam biota benthos atau hewan yang hidup pada dasar perairan (Hermi et al, 2021;Ramadhaniaty et al, 2021;Sarong et al, 2022) .…”
Section: Pendahuluanunclassified
“…Several studies on clams in Indonesia have been reported, including the distribution and diversity in the intertidal zone in Gresik Regency (Zarkasyi et al, 2016), the Lapindo Mud disposal area (Insafitri, 2010), Waemulang beach (Samson et al, 2020), Seagrass ecosystem in the waters of Jepara (Riniatsih and Widianingsih, 2007). Meanwhile, several studies of clams that have been carried out in Aceh include diversity, habitat characteristics and community structure in the mangrove ecosystem of Kampung Jawa Banda Aceh (Ramadhaniaty et al, 2020), coastal areas of Aceh Jaya Regency (Hermi et al, 2021), and coastal areas Teluk Nibung, Pulau Banyak District, Aceh Singkil Regency (Syahputra et al, 2017). However, the safety of clams as food and its ecology (water and sediment) has never been carried out in the Teunom River so that it has a high urgency level.…”
Section: Introductionmentioning
confidence: 99%